A herança forçada e seus reflexos na autonomia do testador: uma análise crítica sobre a imposição da legítima - Ana Carolina de Mari Rocha Benício Carvalho (2022)
In the current social and legal context, this dissertation examines whether the maintenance of the forced heirship in Brazil is still adequate and an option to achieve the aim by its imposition. Therefore, the reasons invoked to justify the forced heirship were critically analyzed, as well as its structure and function. The limits of the Brazilian State intervention in the autonomy of the testator were also reflected together with an investigation of private autonomy and of the functionalization of property right in the succession law. Additionally, more flexible and protective succession models were investigated. Through methodological-dogmatic and descriptive-inductive approaches, it was concluded that forced heirship is inadequate to Brazilian Law in comparison with the new social groups and with other more adequate and constitutional models. After the conclusion, with the confirmation of the need to change the current succession system, some elements were presented for the construction of a theoretical model that serves as a basis for a legislative debate about the subject in Brazil.